Ministry of Commerce and Industry Decree No. 273 For The Year 2021 = وزارة التجارة والصناعة قرار رقم 273 لسنة 2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic